Mananamkan Sikap Moderasi Beragama Melalui Pendidikan Agama Kristen Di SMAN 1 Bintan Timur - Evans Dusep Dongoran; Johanes Waldes Hasugian; Josanti Josanti; Alex Djuang Papay (Institut Kristen Teologi Real Batam, 2020)
Religious moderation is a religious attitude that is balanced between the practice of one's own religion and respect for the religious practices of other people with different beliefs. The attitude of religious moderation must be instilled from an early age among students, in the midst of the development of radical understanding among students. For Christian students, religious moderation is instilled through Christian education which is centred on Jesus. So that through the example of Jesus, students can have a balanced attitude between loving God and others, having an attitude of tolerance and respecting differences.Â AbstrakModerasi beragama adalah sikap beragama yang seimbang antara pengamalan agama sendiri dan penghormatan kepada praktik beragama orang lain yang berbeda keyakinan. Sikap Moderasi beragama harus ditanamkan sejak dini dikalangan pelajar, ditengah berkembangnya paham radikal dikalangan pelajar. Bagi pelajar Kristen Moderasi beragama ditanamkan melalui pendidikan Agama Kristen yang perpusat kepada Yesus. Sehingga melalui teladan Yesus para pelajar dapat memiliki sikap keseimbangan antara mengasihi Allah dan sesama, memiliki sikap toleransi dan menghargai perbedaan.